ANALISIS LETAK GEDUNG SERTA TATA RUANG DINAS KEARSIPAN DAN PERPUSTAKAAN KABUPATEN KUBU RAYA - Towang, Wiranto; Priyadi, Antonius Totok (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study was discussed about the analysis of building area and the layout of the Kubu Raya Archives and Library Service. The purpose of this study was to find out the planning of building construction and public library layout Kubu Raya. To get the data in case to complete the needed data of this the study, the author used qualitative research methods as well as data collection techniques by direct observation in the field, interviews, and documentation. The numbers of informants in this study were consisted of 3 people, namely the Chairman of Kubu Raya Libra ry, the chairman of the mobile library field, and the library manager or librarian. The results of the analysis showed that the located of  Kubu Raya District Archives and Library Office building is in a non-strategic area and does not have library directions, and covered up by other institutions such as the Education Office and Health Office so that most people did not realize about that. The public library building area of Kubu Raya Regency is still inadequate because the standard library building area according to the National Library (National Library Standards) is at least 0.008 m2 but the area of the Library and Library Office building in Kubu Raya Regency only has 8 x 24 m2 building area, 8 rooms area x 12 m2, and room length 12 m2, this is because there is still one building with the Office of Archives, as well as the rooms that are still lacking such as reading room, children's reading room, reference room itself is still in one room, mobile library section headroom mixes up with the processing room, so that it can disrupt the performance of librarians in the library. For now, the chairman of Kubu Raya library has planned to build a new library building. Keywords: Analysis, Building, Spatial Planning, Public Library